LOW DRAUGHT SUBSOIL TILLAGE FACILITIES - Valery Petrovich Kalinichenko; Vladimir Konstantinovich Sharshak; Evgeny Panteleymonovich Ladan; Victor Vasilyevich Illarionov; Evgeny Dmitriyevich Genev (Advanced Engineering Research, 2014)
The biogeosystem engineering is considered, and the verification of the biological, recreational, productive-economic resources of the soil-reclamation agrotechnics based on the rotary milling subsoiling is performed. The test data of the first-generation rotary milling subsoiling facility is provided. A fundamentally new engineering solution is developed. The structural synthesis of the new rotary milling subsoiling facility options in the second- and third-order approximations is performed. The draught minimization of the new facility under its operation is provided. The optimization criterion for the engineering solution synthesis results is developed; the facility parametric synthesis is performed; comparative energy characteristics of the new facility and prototype are given. The rotary milling chisel plough—gearbox transmits torque without passive draught to the tillage tool, and to the subsoiling one that operates full dip being horizontally located and moving progressively at the given depth of 20‒48 cm. The possibility of the reliable operation in the soil of the new engineering solution interconnect system is proved. The assignment and reliability indices of the subsoiling rotary milling facilities are given. Performance physics and physics of failures are considered; the new engineering solution reliability is proved. The fundamentally new principles of the innovation project development and the implementation of the land development plans in Russia are proposed.